2022
DOI: 10.1002/jlb.2ri0122-039r
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of T cells by Polycomb group proteins

Abstract: T cells are critical for pathogen elimination, tumor surveillance, and immunoregulation. The development, activation, and differentiation of CD8 and CD4 T lymphocytes are a set of complex and dynamically regulated events that require epigenetic control. The Polycomb group (PcG) proteins are a family of diverse and evolutionarily conserved epigenetic modulators fundamentally involved in several mechanisms of gene regulation. PcG proteins can assemble into distinct repressor complexes, the two most understood be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 148 publications
0
2
0
Order By: Relevance
“…PRC1 is associated with tumor proliferation, metastasis, and tumorigenesis. It is highly expressed in multiple tumors and is regulated by nuclear β-catenin and WNT expression[ 62 ]. Additionally, some studies have reported that PRC1 controls chromatin structure mainly through posttranslational histone modifications.…”
Section: Discussionmentioning
confidence: 99%
“…PRC1 is associated with tumor proliferation, metastasis, and tumorigenesis. It is highly expressed in multiple tumors and is regulated by nuclear β-catenin and WNT expression[ 62 ]. Additionally, some studies have reported that PRC1 controls chromatin structure mainly through posttranslational histone modifications.…”
Section: Discussionmentioning
confidence: 99%
“…H3K27me3 can recruit another epigenetic complex from the Polycomb group (PcG), the PRC1, that also works as a repressor through the ubiquitylation of lysine 119 of histone H2A (H2AK119ub) by its catalytic subunit Ring1, as well as through chromatin remodeling mechanisms mediated by other subunits that can integrate the complex (32). PRC1 composition is highly heterogeneous, and its distinct configurations are divided in canonical (cPRC1) or noncanonical PRC1 (ncPRC1) (33, 34). While ncPRC1 complexes can be recruited to genome sites independently of PRC2 function (35, 36), cPRC1 are known to be recruited to H3K27me3-tagged loci .…”
Section: Introductionmentioning
confidence: 99%